Role of Pressures and Green Supply Chain Management Practices in Enhancing the Operational Efficiency of Firms: Evidence from Thailand - Sudawan Somjai; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
The environmental challenges for business are on rise. Bearing this fact in mind current has explored the relationship between different pressures and green supply chain management practices (GSCMP). In addition current study has considered the GSCMP as a mediator. 220 respondents participated in the study and Smart-PLS was used for data analysis. Results revealed positive link between coercive, normative, mimetic pressure and GSCMP. Furthermore the study also revealed that GSCMP significantly and positively mediates the relationship between coercive, normative, mimetic pressure and operational efficiency. The study concluded that when an organization is forced through the external sources such as legislation, environment protection agencies and customers they tend to follow the GSCMP. These practices in turn lead towards the operational efficiency of the firms. The limitations and future research areas are provided in the study.